∫ 3 1 5 − 1 5 − 1 x + 1 4 x 2 + 8 x − 1 d x
If the definite integral above can be expressed in simplest form as d a b − c π , find the value of a + b + c + d .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
First we simplify the expression under the square root by completing the square:
4 x 2 + 8 x − 1 = 4 ( x 2 + 2 x ) − 1 = 4 [ ( x + 1 ) 2 − 1 ] − 1 = 4 ( x + 1 ) 2 − 5 .
Next, we make the substitution x = 2 5 sec θ − 1
⇒ d x = 2 5 sec θ tan θ d θ
With a change of variable, we must also change the limits of integration:
When x = 3 1 5 − 1 , θ = 6 π , and when x = 5 − 1 , θ = 3 π .
Hence the integral becomes:
∫ 6 π 3 π 2 5 sec θ 4 ⋅ 4 5 sec 2 θ − 5 ⋅ 2 5 sec θ tan θ d θ = ∫ 6 π 3 π 5 ( sec 2 θ − 1 ) ⋅ tan θ d θ = 5 ∫ 6 π 3 π ∣ tan θ ∣ ⋅ tan θ d θ
Since tan θ > 0 for our limits, we take the positive root and drop the absolute value bars, giving 5 ∫ 6 π 3 π tan 2 θ d θ .
Using the substitution tan 2 θ = sec 2 θ − 1 , the integral becomes
5 [ tan θ − θ ] 6 π 3 π = 6 4 1 5 − 5 π .
Hence, a = 4 , b = 1 5 , c = 5 and d = 6 , and a + b + c + d = 3 0 .